Buddhism and Linguistics Theory and Philosophy (Springer International Publishing, 2018)
This edited collection brings linguistics into contact with a millennia of works by Buddhist scholars. Examining the Buddhist contemplative tradition and its extensive writings from an interdisciplinary perspective, the authors bridge the gap between such customs and human language. To do so, they provide chapters on linguistics, history, religious studies, philosophy and semiotics. Uniting scholars from three different continents and from many disciplines and institutions, this innovative and unique book is sure to appeal to anyone interested in Buddhist traditions and linguistics.